Types of bread preferred by adult individuals and bread's place in daily nutrition - Yoldaş İlktaç, Havvanur; Sadık, Merve; Garipağaoğlu, Muazzez (Mattioli 1885, 2021)
Bread, one of the most consumed food by humankind throughout history, has a global importance in nutrition. The common belief in recent years that bread is fattening and is harmful to health causes bread to be excluded from daily nutrition. This study aims to determine the individuals' bread preferences and the contribution of the bread consumed to daily nutrition. It was carried out in Turkey with 1766 volunteer participants aged between 18-65 years. The data were collected with a questionnaire form applied by face-to-face interview method. In order to determine the nutritional status, 2-day food consumption records were kept. The body mass index average of individuals was 26.4 +/- 8.25 kg/m(2). The waist circumference averages of male and female participants were found as 97.8 +/- 12.97 cm, 91.1 +/- 16.13 cm, respectively. It was found that the most consumed bread was white bread (87.3%), followed by whole-grain bread (40.8%). It has been found that the consumption of whole grain bread is higher in women compared to men. Female participants' whole-grain bread consumption was found to be higher than male participants, while male participants' cornbread consumption was higher than female participants (p<0.00 and p=0.026). It was found that male participants consume 182.3 +/- 105.07 g of bread per day, while females 124.5 +/- 78.11 g. It was observed that bread constitutes 27.1% of total daily energy intake in male participants, while 22.1% in females and this difference was found statistically significant (p<0.001). These results reveal that bread is the main ingredient in nutrition for Turkish society. The type of bread, which makes up the majority of carbohydrates, is as important as the amount. It is thought that training on healthy consumption of bread at the national level, and national and public service announcements and government-backed activities can positively change the bread consumption habits of individuals.
Keywords: Bread; Nutrition; Health; Diet; Grains